Eficacy of non-woven geotextile as separator for drainage media sandwiching dredged marine clay - Siti Farhanah, SM Johan; Chan, Chee Ming (Penerbit UTHM, 2024)
Geotextile had been used widely in the constructions and functioning as separator, filtration and reinforcement. This study work on the experimental on the dredged sediments from dredging activities. The sediments were called as dredged marine soils (DMS) which is too soft, slurry and have poor engineering properties. Therefore, it considered as geo-waste. Laboratory testing was performed to determine the preliminary effect on both conditions of drainage layer, either with or without separator between POC or RPM drainage layer and DMS. The results showed that non-separator have more settlement compared to specimens with separator. In addition, RPM (separator) dissipates water faster compared to others specimens. Although POC are known to be good drainage, crushing tendency of POC influenced the time of consolidation, which almost like POC (non-separator). In conclusion, the use of geotextile indicates a good potential to be applying on the land reclamation and embankment as well.